Relationship between intrinsic connections and functional architecture revealed by optical imaging and in vivo targeted biocytin injections in primate striate cortex. - Malach, R (1993)
In primate primary visual cortex, neurons sharing similar response properties are clustered together forming functional domains that appear as a mosaic of patches or bands, often traversing the entire cortical depth from the pia to the white matter. Similarly, each cortical site connects laterally through an extensive network of intrinsic projections that are organized in multiple clusters (patches) and reach distances of up to a few millimeters. The relationship between the functional domains and these laterally connected patches has remained a controversial issue despite intensive research efforts. To investigate this relationship, we obtained high-resolution functional maps of the cortical architecture by in vivo optical imaging. Subsequently, extracellular injections of the sensitive anterograde tracer biocytin were targeted into selected functional domains. Within the ocular dominance system, we found that long-range intrinsic connections tended to link the monocular regions of same-eye ocular dominance columns. Furthermore, we discovered that binocular domains formed a separate set of connections in area V1; binocular regions were selectively connected among themselves but were not connected to strictly monocular regions, suggesting that they constitute a distinct columnar system. In the other subsystem subserving orientation preference, patches of intrinsic connections tended to link domains sharing similar orientation preferences. Analyses of the precision of these connections indicated that in both functional subsystems, < 15% of the connections were between domains having orthogonal response properties. However, their selectivity was limited; approximately 30% +/- 10% of the interconnected patches contained neurons exhibiting orientation tuning that differed from those found at the injection sites by at least 45 degrees. At short range (up to 400 microns from the injection site), this casual trend seemed markedly accentuated; the local, synaptic-rich axonal and dendritic arbors crossed freely through columns of diverse functional properties. These complex sets of connections can endow cortical neurons with a rich diversity of response properties and broad tuning.